2018
DOI: 10.1007/s10546-018-0395-x
|View full text |Cite
|
Sign up to set email alerts
|

Biases in Model-Simulated Surface Energy Fluxes During the Indian Monsoon Onset Period

Abstract: 2019. Biases in modelsimulated surface energy fluxes during the Indian monsoon onset period. 170 (2).Abstract We use eddy covariance measurements over a semi-natural grassland in the cen-8 tral Indo-Gangetic Basin to investigate biases in the energy fluxes simulated by the Noah 9 land-surface model (LSM) for two monsoon onset periods: one with rain (2016) and one 10 completely dry (2017). In the preliminary run with default parameters, the offline Noah 11 LSM overestimates the midday (1000 to 1400 local time)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 75 publications
0
13
0
Order By: Relevance
“…Of the land surface models (LSMs) taking part in the LUMIP (Lawrence et al., 2016), at least three still use the one‐big‐leaf scheme (Table 3). Likewise, the land surface modules in regional weather models usually have the simplistic one‐big‐leaf type representation of the vegetation (Davin & Seneviratne, 2012) or even combined vegetation and ground surface layers (Chakraborty et al., 2019). Thus, regional studies on aerosol impact on the surface energy budget using these models evidently miss this key mechanism (Li et al., 2017; Pere et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Of the land surface models (LSMs) taking part in the LUMIP (Lawrence et al., 2016), at least three still use the one‐big‐leaf scheme (Table 3). Likewise, the land surface modules in regional weather models usually have the simplistic one‐big‐leaf type representation of the vegetation (Davin & Seneviratne, 2012) or even combined vegetation and ground surface layers (Chakraborty et al., 2019). Thus, regional studies on aerosol impact on the surface energy budget using these models evidently miss this key mechanism (Li et al., 2017; Pere et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have noted that the seasonality of the UHI in this region is influenced by the variability in surface vegetation in the rural area [17,18]. Agricultural influence on surface climate in this region is not well-captured by LSMs due to inaccurate representation of vegetation properties and the poorly constrained influence of irrigation on the hydrological cycle [10,19]. Thus, beyond the widely studied changes in atmospheric composition [20,21], the lockdowns provide a unique opportunity to ask broader questions about human-land-atmosphere interactions in the IGB.…”
Section: Introductionmentioning
confidence: 99%
“…At smaller scales, Barton et al (2020) have demonstrated that gradients in soil moisture, whether caused by antecedent rainfall or irrigation practices, lead to mesoscale convergence patterns that can initiate storms. Finally, using the IIT Kanpur flux tower observations, Chakraborty et al (2019) found that the NOAH land-surface model significantly underestimates the latent-heat flux over the region during the monsoon onset period, which was partly addressed by improving the vegetation parametrization in the model.…”
Section: Emerging Resultsmentioning
confidence: 99%
“…Finally, using the IIT Kanpur flux tower observations, Chakraborty et al . () found that the NOAH land‐surface model significantly underestimates the latent‐heat flux over the region during the monsoon onset period, which was partly addressed by improving the vegetation parametrization in the model.…”
Section: Discussionmentioning
confidence: 99%